Process-Dependent Variations in the Proliferation of Myoblasts, Fibroblasts and Chondrocytes on Laser-Sintered Polypropylene - Detsch, Rainer; Schlicht, Samuel; Nawaz, Qaisar; Boccaccini, Aldo R.; Drummer, Dietmar (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2025)
Additively manufactured polyolefins find broad applications in medical engineering, enabling the manufacturing of patient-specific geometries. For investigating the influence of processing conditions of laser sintered locally macroporous polypropylenesubstrates, the response of myoblasts, chondrocytes, and fibroblasts has been characterized in this study. An influence of the applied manufacturing parameters on the attachment and viability of the investigated cells is observed, showing the effect of the superficial pore topology on the attachment and the spreading of cells. The viability and attachment of fibroblasts and chondrocytescould be improved by reducing the thermal exposure during the processing step of the dense base part, associated with increasedsuperficial porosity and the corresponding increase of the surface area. The applied additive manufacturing process of macropo-rous structures influences emerging cell morphologies, leading to an extended morphological expression of chondrocytes and theovergrowth of small pores by fibroblasts. This indicates an improvement in superficial cell adhesion due to larger pores. These findings indicate the significance of the processing conditions in laser sintering of polypropylene on the cell response throughthe optimization of processing parameters and the attachment of an open-cell pore structur
Keywords: biopolymers; cell attachment; laser-sintering; macroporous polypropylene